The UK Productivity Shortfall in an Era of Rising Labour Supply - Andrew Benito; Garry Young (Institute of Labor Economics (IZA), 2021)
Labour productivity stagnated in the UK in the years between the financial crisis and the emergence of Covid-19. At the same time labour supply and employment grew strongly, driven primarily by net inward migration. While labour productivity should be independent of labour supplied in the long run, this need not be the case in the medium-run. Our evidence suggests that around one-fifth, or 4pp, of the 25 log point fall in productivity from its previous trend can be explained by increased labour supply, with idiosyncratic factors and a slowdown in TFP growth accounting for most of the shortfall.
Keywords: J11; J21; D24; 330; productivity; labour supply; capital deepening